2022
DOI: 10.3390/plants11020148
|View full text |Cite
|
Sign up to set email alerts
|

Development of Hairy Root Cultures for Biomass and Triterpenoid Production in Centella asiatica

Abstract: Centella asiatica (Apiaceae) is a tropical/subtropical medicinal plant, which contains a variety of triterpenoids, including madecassoside, asiaticoside, madecassic acid, and asiatic acid. In this study, we tested the efficiency of hairy root (HR) induction in C. asiatica from leaf and petiole explants. Leaves and petioles collected from C. asiatica plants were suspended in agro-stock for 30 min and co-cultured with Agrobacterium rhizogenes for 3 days to induce HR formation. The transformation efficiency of le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Studies have shown that among the many factors that determine the efficiency of genetic transformation by the leaf disc method, plant species and genotypes within the same species may have greater influence [ 31 34 , 73 ]. The use of different explants and explants at different development stages has a great impact on transformation efficiency [ 6 , 7 , 19 , 35 , 37 40 ]. This indicates that the optimal genetic transformation period must be different for different species, different genotypes of the same species, different explants of the same genotype, and receptor materials of the same explant at different developmental stages when transformation is applied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that among the many factors that determine the efficiency of genetic transformation by the leaf disc method, plant species and genotypes within the same species may have greater influence [ 31 34 , 73 ]. The use of different explants and explants at different development stages has a great impact on transformation efficiency [ 6 , 7 , 19 , 35 , 37 40 ]. This indicates that the optimal genetic transformation period must be different for different species, different genotypes of the same species, different explants of the same genotype, and receptor materials of the same explant at different developmental stages when transformation is applied.…”
Section: Discussionmentioning
confidence: 99%
“…Agrobacterium tumefaciens -mediated leaf disc transformation is a plant genetic transformation method developed by Horsch et al [ 4 , 5 ]. The improved leaf disc method includes stem segments, petioles, hypocotyls, cotyledons, and other explant materials [ 6 , 7 ]. This method introduces foreign DNA fragments or gene editors carried by Ti plasmids, Ri plasmids, and other carriers into host cells through Agrobacterium infection to study related gene functions or realize plant breeding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of the biological industry in recent years, the cost of metabolome, transcriptome and genome research has greatly reduced. Hairy root cultures are being gradually applied to the study of metabolic pathways [ 43 , 44 , 45 , 46 , 47 ]. Nonetheless, our results indicate that ABA inhibited PA biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…More than 300 species of hairy roots have been established in the culture system and used to produce bioactive compounds. Of these, 76% are herbaceous plants, such as the sunflower Helianthus annuus L. [ 14 ], as well as Urena lobata [ 15 ] and Centella asiatica [ 16 ]. Because of the difficulty in infecting woody plants and lianas, woody plants such as Taxus × media have accounted for 17% [ 17 ], while lianas such as Tripterygium wilfordii have accounted for 7% [ 18 ].…”
Section: Introductionmentioning
confidence: 99%